2010
DOI: 10.1111/j.1442-2042.2010.02570.x
|View full text |Cite
|
Sign up to set email alerts
|

Radical prostatectomy in obese patients: Improved surgical outcomes in recent years

Abstract: Objectives: Obesity has been proposed as a risk factor for reduced disease-specific survival, increased positive surgical margin (PSM) and biochemical recurrence (BCR) after radical prostatectomy (RP) in patients with prostate cancer. The aim of this study was to clarify the relationship between obesity and surgical outcomes in patients undergoing RP. Methods: Medical records of 491 patients who underwent RP from 2004 to 2007 were retrieved from our institutional database. Patients were divided into three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Open radical retropubic prostatectomy in obese patients was described by Lindner [13]. While the incidence of perioperative complications and blood transfusions was similar, the authors found that EBL was higher in the obese group and operative times in the obese were longer.…”
Section: Discussionmentioning
confidence: 96%
“…Open radical retropubic prostatectomy in obese patients was described by Lindner [13]. While the incidence of perioperative complications and blood transfusions was similar, the authors found that EBL was higher in the obese group and operative times in the obese were longer.…”
Section: Discussionmentioning
confidence: 96%
“…Even minor surgical complications, such as wound infections and lymphedema, can result in increased cost, reduced quality of life for patients, and delays in the receipt of adjuvant therapy, such as chemotherapy and radiation. Among patients with prostate cancer, 1 study demonstrated that surgical time was prolonged and blood loss was greater in obese patients, although these factors did not translate into higher transfusion rates . Another study reported that obesity was associated with an increased risk of having positive surgical margins after radical prostatectomy, which, in turn, are associated with an increased risk of recurrence, poor outcomes, and a potential need for additional adjuvant treatment …”
Section: Obesity and Cancer‐directed Surgerymentioning
confidence: 99%
“…Among patients with prostate cancer, 1 study demonstrated that surgical time was prolonged and blood loss was greater in obese patients, although these factors did not translate into higher transfusion rates. 13 Another study reported that obesity was associated with an increased risk of having positive surgical margins after radical prostatectomy, 14 which, in turn, are associated with an increased risk of recurrence, poor outcomes, and a potential need for additional adjuvant treatment. 15 OBESITY AND RADIATION THERAPY Radiation therapy uses targeted ionizing radiation to destroy tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Several studies have reported a correlation between operating time or blood loss and BMI in laparoscopic nephrectomy. [11][12][13] Transperitoneal laparoscopic renal surgery for obese patients with a BMI of 30 kg/m 2 or greater had longer operative times and increased blood loss compared with the same procedure in non-obese patients.…”
Section: Discussionmentioning
confidence: 98%